Building the minimum viable transformation in Indonesia: Evidence from firms and women-led MSMEs - Adiputri, Zulfa Utami (Privietlab, 2024)
This study slide-based teaching materials on digital transformation into a measurement-ready, Minimal Viable Transformation (MVT) architecture spanning five basics – strategy and culture, staff and customer engagement, process and innovation, digital technology, and data and analytics – with inclusion embedded as a capability risk control. Using a concise mixed-methods design, we generated indicators from interviews and a focused workshop, validated a multi-respondent survey linked to lightweight telemetry (event coverage, release cadence, CSAT/NPS), and piloted 90-day improvement bundles. The results show that a one-standard-deviation rise in MVT is associated with higher customer trust/experience and operational performance and, where available, growth/margin uplift. Decomposition highlights Data & Analytics and Process & Innovation as primary levers for operations, while Strategy & Culture and Staff & Customer Engagement explain trust and experience. Dynamic capabilities and data-driven decision-making act as mechanisms, and inclusion amplifies effects, especially in women-led MSMEs, where lightweight stacks (mobile storefronts, simple OKRs, SKU-level analytics) produce measurable gains. The contribution is a parsimonious, sequenced, and auditable blueprint that turns “digital talk” into weekly behaviors that leaders can govern and scale in resource-constrained contexts.